Coreceptor Scanning by the T Cell Receptor Provides a Mechanism for T Cell Tolerance - Stepanek, Ondrej; Prabhakar, Arvind S.; Osswald, Celine; King, Carolyn G.; Bulek, Anna; Naeher, Dieter; Beaufils-Hugot, Marina; Abanto, Michael L.; Galati, Virginie; Hausmann, Barbara; Lang, Rosemarie; Cole, David K.; et al. (Cell, 2014)
In the thymus, high-affinity, self-reactive thymocytes are eliminated from the pool of developing T cells, generating central tolerance. Here, we investigate how developing T cells measure self-antigen affinity. We show that very few CD4 or CD8 coreceptor molecules are coupled with the signal-initiating kinase, Lck. To initiate signaling, an antigen-engaged T cell receptor (TCR) scans multiple coreceptor molecules to find one that is coupled to Lck; this is the first and rate-limiting step in a kinetic proofreading chain of events that eventually leads to TCR triggering and negative selection. MHCII-restricted TCRs require a shorter antigen dwell time (0.2 s) to initiate negative selection compared to MHCI-restricted TCRs (0.9 s) because more CD4 coreceptors are Lck-loaded compared to CD8. We generated a model (Lck come&stay/signal duration) that accurately predicts the observed differences in antigen dwell-time thresholds used by MHCI- and MHCII-restricted thymocytes to initiate negative selection and generate self-tolerance. [Display omitted] •TCR scans multiple coreceptors to initiate a TCR signal and negative selection•Frequency of Lck loaded coreceptors sets antigen dwell-time threshold•Shorter antigen dwell-time threshold for pMHCII compared to pMHCI self-antigens•“Lck come&stay/signal duration” model explains how the TCR reads antigen dwell time A combination of experimental approaches and mathematic modeling reveals how T cells measure affinity for self-antigens in the thymus to generate self-tolerance.